Failure of Repeated Electroconvulsive Shock Treatment on 5-HT4-Receptor-Mediated Depolarization Due To Protein Kinase A System in Young Rat Hippocampal CA1 Neurons - Kumatoshi Ishihara; Masashi Sasa (Elsevier, 2004)
We previously demonstrated that repeated electroconvulsive shock (ECS) treatment enhanced serotonin (5-HT)1A- and 5-HT3-receptor-mediated responses in hippocampal CA1 pyramidal neurons. The electrophysiological studies were performed to elucidate the effects of ECS treatment on depolarization, which was an additional response induced by 5-HT, and the second messenger system involved in this depolarization of hippocampal CA1 neurons. Bath application of 5-HT (100 μM) induced depolarization of the membrane potential in the presence of 5-HT1A-receptor antagonists. This depolarization was mimicked by 5-HT4-receptor agonists, RS 67506 (1 - 30 μM) and RS 67333 (0.1 - 30 μM), in a concentration-dependent manner. 5-HT- and RS 67333-induced depolarization was attenuated by concomitant application of RS 39604, a 5-HT4-receptor antagonist. H-89, a protein kinase A (PKA) inhibitor, inhibited 5-HT-, RS 67506-, and RS 67333-induced depolarizations, while forskolin (10 μM), an activator of adenylate cyclase, induced depolarization. Furthermore, RS 67333-induced depolarization was not significantly different between hippocampal slices prepared from rats administered ECS once a day for 14 days and those from sham-treated rats. These findings suggest that 5-HT4-receptor-mediated depolarization is caused via the cAMP-PKA system. In addition, repeated ECS-treatment did not modify 5-HT4-receptor functions in contrast to 5-HT1A- and 5-HT3-receptor functions. Keywords:: serotonin (5-HT), 5-HT4 receptor, depolarization, hippocampal CA1 region, electroconvulsive shock